Anticoagulant therapy in pediatrics - Dabbous, Mariam K. (Medknow Publications & Media Pvt Ltd, 2014)
Thromboembolic episodes are disorders encountered in both children and adults, but relatively more common in adults. However, the occurrence of venous thromboembolism and use of anticoagulants in pediatrics are increasing. Unfractionated Heparin (UH) is used as a treatment and prevention of thrombosis in adults and critically ill children. Heparin utilization in pediatric is limited by many factors and the most important ones are Heparin Induced Thrombocytopenia (HIT) and anaphylaxis. However, Low Molecular Weight Heparin (LMWH) appears to be an effective and safe alternative treatment. Hence, it is preferred over than UH due to favorable pharmacokinetic and side effect profile. Direct Thrombin Inhibitors (DTI) is a promising class over the other anticoagulants since it offers potential advantages. The aim of this review is to discuss the differences between adult and pediatric thromboembolism and to review the current anticoagulants in terms of pharmacological action, doses, drug reactions, pharmacokinetics, interactions, and parameters. This review also highlights the differences between old and new anticoagulant therapy in pediatrics.